From theory to practice - West-Burnham, John (Vodenje v vzgoji in izobraževanju, 2014)
The purpose of this paper is to explore the conceptual issues in reconciling theory and practice in leadership development. The central concern of the study is the perceived issue that there is limited confidence that the prevailing orthodoxies influencing leadership development programmes actually translate into changed behaviour. The paper explores the epistemological issues in analysing the interaction between theory and practice and then reviews the evidence for the relative impact of different approaches to leadership development. A central theme of the discussion is the nature of personal constructs and how they relate to personal learning and professional development.
Keywords: development; education; leadership; learning strategies; personal constructs; practice; profesionalni razvoj; ravnatelji; theory; učne strategije; vodenje